The Key Associated Factor of the Emergence of the Dengue Vector in Peri-Urban and Rural Settlements - Ayu Dewi Wiyata; Wahyu Handoyo; Sayono Sayono (JURNAL KESEHATAN LINGKUNGAN, 2023)
Introduction: The population density of Aedes mosquitoes is a risk factor for dengue in endemic areas. Therefore, it is necessary to understand the risk factors for mosquito vector emergence in settlements. This study aimed to determine the key factors associated with the occurrence and population density of dengue vectors in peri-urban and rural settlements. Methods: A cross-sectional study was conducted in two dengue-endemic villages, Bergas-Kidul and Gebugan, representing peri-urban and rural settlements, respectively. A cluster-based larval survey was conducted in the dengue-case house and in 18–20 houses around a radius of 100 m. All water containers and their characteristics and mosquito larvae emergence were recorded in each house to calculate Aedes indices. The geographic coordinates, altitude, air temperature, and humidity were mapped and analyzed using GIS and SPSS software. Results and Discussion: Dengue vectors were found in peri-urban and rural with HI, CI, BI, and DF indices of 29.3%, 32.2%, 35.4, 6.0; then 12.2%, 14.3%, 14.6, and 3.0, respectively. In peri-urban areas, larval occurrence was associated with air temperature, air humidity, container type, and open microhabitat, whereas in rural areas, it was associated with only open microhabitat. Conclusion: The Aedes indices represent a high density of mosquito populations, and the existence of open microhabitats is the key factor for larval occurrence in both peri-urban and rural settlements. Community participation in vector control needs to be increased in addition to studying the resistance of Aedes mosquitoes to a number of insecticide groups.